The Influence of Social Media and Anxiety on Students’ Understanding of Learning: A Case Study - Rizal Afif A. Napitupulu; Ardelia Suharmanto; Lucy LS (Universitas Negeri Medan, 2026)
The rapid development of information and communication technology has increased the intensity of social media use, especially among students. Although social media provides various benefits, excessive use can have negative psychological impacts such as anxiety and student learning comprehension. This study aims to analyze the influence of social media use and social anxiety on the learning comprehension of students majoring in Business Administration at Sriwijaya State Polytechnic, Palembang. This study uses a quantitative approach with a survey method. Data were collected from students through an online questionnaire distributed via Google Forms. Data analysis will use the multiple linear regression method. The sample of this study was 103 students of Sriwijaya State Polytechnic Bukit class. This research method used regression. Social media, anxiety, and learning comprehension were measured and collected using a questionnaire with a Lickert scale. Then, the data were analyzed using SPSS software. The results and conclusions show that social media and anxiety have an influence on student learning comprehension. The regression analysis found that social media contributed to learning comprehension (β = 0.159, p < 0.05) and anxiety also contributed to learning comprehension (β = 0.213, p < 0.05). The findings of this study are expected to provide students with insight into using social media more wisely.